MYB and bHLH transcription factor transgenes increase anthocyanin pigmentation in petunia and lisianthus plants, and the petunia phenotypes are strongly enhanced under field conditions - Schwinn, Kathy E.; Boase, Murray R.; Bradley, J. Marie; Lewis, David H.; Deroles, Simon C.; Martin, Cathie R.; Davies, Kevin M. (Frontiers in Plant Science, 2014)
Petunia line Mitchell [MP, Petunia axillaris × (P. axillaris × P. hybrida)] and Eustoma grandiflorum (lisianthus) plants were produced containing a transgene for over-expression of the R2R3-MYB transcription factor (ROSEA1) that up-regulates flavonoid biosynthesis in Antirrhinum majus. The petunia lines were also crossed with previously produced MP lines containing a Zea mays flavonoid-related bHLH transcription factor transgene (LEAF COLOR, LC), which induces strong vegetative pigmentation when these 35S:LC plants are exposed to high light levels. 35S:ROS1 lisianthus transgenics had limited changes in anthocyanin pigmentation, specifically, precocious pigmentation of flower petals and increased pigmentation of sepals. RNA transcript levels for two anthocyanin biosynthetic genes, chalcone synthase and anthocyanidin synthase, were increased in the 35S:ROS1 lisianthus petals compared to those of control lines. With MP, the 35S:ROS1 calli showed novel red pigmentation in culture, but this was generally not seen in tissue culture plantlets regenerated from the calli or young plants transferred to soil in the greenhouse. Anthocyanin pigmentation was enhanced in the stems of mature 35S:ROS1 MP plants, but the MP white-flower phenotype was not complemented. Progeny from a 35S:ROS1×35S:LC cross had novel pigmentation phenotypes that were not present in either parental line or MP. In particular, there was increased pigment accumulation in the petal throat region, and the anthers changed from yellow to purple colour. An outdoor field trial was conducted with the 35S:ROS1, 35S:LC, 35S:ROS1×35S:LC and control MP lines. Field conditions rapidly induced intense foliage pigmentation in 35S:LC plants, a phenotype not observed in control MP or equivalent 35S:LC plants maintained in a greenhouse. No difference in plant stature, seed germination, or plant survival was observed between transgenic and control plants.